Immunopathological study of spleen during Japanese encephalitis virus infection in mice. - Mathur, A. (1988)
Following intraperitoneal inoculation, Japanese encephalitis virus replicated in peritoneal macrophages, appeared on day 3 in the splenic macrophages of the perifollicular region and later in cells of the periarteriolar lymphoid sheath (PALS) as shown by indirect immunofluorescence. Productive JEV infection was observed both in macrophages and T-cells. Morphological study of spleen during JEV infection revealed proliferative changes, with increased number of macrophages from day 3 p.i. in the perifollicular region followed by accumulation of polymorphonuclear leucocytes which reached a maximum on day 9 p.i. The T dependent areas were considerably enlarged by day 9 and gradually reduced in size by week 3. At later periods germinal centres appeared in the T independent area and were prominent by day 15. The cells containing virus antigen disappeared with the appearance of germinal centres, thus indicating the role of the latter also in virus clearance.